Biological control of locusts and grasshoppers - Lomer, C.J.; Bateman, R.P.; Johnson, D.L.; Langewald, J.; Thomas, M. (Annual Reviews, 2001)
Control of grasshoppers and locusts has traditionally relied on synthetic insecticides, and for emergency situations this is unlikely to change. However, a growing awareness of the environmental issues associated with acridid control as well as the high costs of emergency control are expanding the demand for biological control. In particular, preventive, integrated control strategies with early interventions will reduce the financial and environmental costs associated with large-scale plague treatments. The recent development of effective oil formulations of Metarhizium anisopliae spores in Africa, Australia, and Brazil opens new possibilities for environmentally safe control operations. Metarhizium biopesticide kills 70%–90% of treated locusts within 14–20 days, with no measurable impact on nontarget organisms. An integrated pest management strategy, with an emphasis on the use of Metarhizium, that incorporates rational use of chemical pesticides with biological options such as the microsporidian Nosema locustae and the hymenopteran egg parasitoids Scelio spp., has become a realistic option.